Toward the assessment of food toxicity for celiac patients: characterization of monoclonal antibodies to a main immunogenic gluten peptide. - Belén Morón (Public Library of Science (PLoS), 2008)
Background and aims Celiac disease is a permanent intolerance to gluten prolamins from wheat, barley, rye and, in some patients, oats. Partially digested gluten peptides produced in the digestive tract cause inflammation of the small intestine. High throughput, immune-based assays using monoclonal antibodies specific for these immunotoxic peptides would facilitate their detection in food and enable monitoring of their enzymatic detoxification. Two monoclonal antibodies, G12 and A1, were developed against a highly immunotoxic 33-mer peptide. The potential of each antibody for quantifying food toxicity for celiac patients was studied. Methods Epitope preferences of G12 and A1 antibodies were determined by ELISA with gluten-derived peptide variants of recombinant, synthetic or enzymatic origin. Results The recognition sequences of G12 and A1 antibodies were hexameric and heptameric epitopes, respectively. Although G12 affinity for the 33-mer was superior to A1, the sensitivity for gluten detection was higher for A1. This observation correlated to the higher number of A1 epitopes found in prolamins than G12 epitopes. Activation of T cell from gluten digested by glutenases decreased equivalently to the detection of intact peptides by A1 antibody. Peptide recognition of A1 included gliadin peptides involved in the both the adaptive and innate immunological response in celiac disease. Conclusions The sensitivity and epitope preferences of the A1 antibody resulted to be useful to detect gluten relevant peptides to infer the potential toxicity of food for celiac patients as well as to monitor peptide modifications by transglutaminase 2 or glutenases.